Anaplastic large T-cell lymphoma: 10-year experience at the National Institute of Neoplastic Diseases, Lima – Peru: Linfoma de células grandes T anaplásico: experiencia de 10 años en el Instituto Nacional de Enfermedades Neoplásicas, Lima - Perú - Pacheco , Cristian (2022)
Introduction: Anaplastic Large T-Cell Lymphoma is an infrequent pathology, determined by the expression of CD30, with different characteristics in its presentation and being more aggressive according to the expression of ALK. Objectives: The present study seeks to determine the epidemiological, clinicopathological and prognostic characteristics of patients with Anaplastic Large T-Cell Lymphoma. Methods: Descriptive, retrospective study of patients diagnosed with Anaplastic Large T-Cell Lymphoma of the National Institute of Neoplastic Diseases (INEN) between 2006 and 2016. Results: The pathology of 86 patients was analyzed and reviewed, 57% were men and 33% women, of the total population 21.9% were positive for ALK. 48 of the patients were found in CD I and II and 36 between stages III and IV. 57 patients had low or low-intermediate risk, while 26 had high-intermediate and high risk. The estimated overall survival was 40.8% at 5 years, in the group of patients with ALK + it was 67.4% and in the group with ALK- it was estimated at 30.2%. Conclusions: Anaplastic Large T-Cell Lymphoma is an aggressive disease, with a heterogeneous distribution with respect to age and slightly more frequent in males, with ALK and the international prognostic index as important prognostic factors.